Metamorphism of the Skarn Rocks from the Sasa Ore Field (Geologica Macedonica, 2013)
The aim of this paper is to define the metamorphism of the skarn rocks from the Sasa ore filed. Inthese rocks ilvaite, rhodonite, bustamite, johansenite-ferrojohansenite, andradite, actinolite-ferroactinolite and epidotewere determined. On the base of the presence minerals associations in studied rocks were determinated three facies:albite-epidote-hornfels facies; hornblende-hornfels facies; K-feldspate-cordierite-hornfels facies. The rocks studiedare formed in temperature condition T 400–800oC and preassure P 1.5–2 kbar.